The use of non-model Drosophila species to study natural variation in TOR pathway signaling. - Steenwinkel, T.E.; Hamre, K.K.; Werner, T. (PLoS ONE, 2022)
Nutrition and growth are strongly linked, but not much is known about how nutrition leads to growth. To understand the connection between nutrition through the diet, growth, and proliferation, we need to study the phenotypes resulting from the activation and inhibition of central metabolic pathways. One of the most highly conserved metabolic pathways across eukaryotes is the Target of Rapamycin (TOR) pathway, whose primary role is to detect the availability of nutrients and to either induce or halt cellular growth. Here we used the model organism Drosophila melanogaster (D. mel.) and three non-model Drosophila species with different dietary needs, Drosophila guttifera (D. gut.), Drosophila deflecta (D. def.), and Drosophila tripunctata (D. tri.), to study the effects of dietary amino acid availability on fecundity and longevity. In addition, we inhibited the Target of Rapamycin (TOR) pathway, using rapamycin, to test how the inhibition interplays with the nutritional stimuli in these four fruit fly species. We hypothesized that the inhibition of the TOR pathway would reverse the phenotypes observed under conditions of overfeeding. Our results show that female fecundity increased with higher yeast availability in all four species but decreased in response to TOR inhibition. The longevity data were more varied: most species experienced an increase in median lifespan in both genders with an increase in yeast availability, while the lifespan of D. mel. females decreased. When exposed to the TOR inhibitor rapamycin, the life spans of most species decreased, except for D. tri, while we observed a major reduction in fecundity across all species. The obtained data can benefit future studies on the evolution of metabolism by showing the potential of using non-model species to track changes in metabolism. Particularly, our data show the possibility to use relatively closely related Drosophila species to gain insight on the evolution of TOR signaling.